BEA-007 What Do Your Employees Think About Total Quality Management Systems?. (12th March 2013) - Haider, D; Klein, K; Bouchand, GPG
Abstract : Background: A Total Quality Management System (TQMS) is being implemented in the pharmacy of a 1456-bed hospital in Vienna, Austria. The hospital pharmacy consists of five departments; dispensary service, clinical pharmacy service, pharmaceutical compounding, cytotoxic reconstitution, medicines information. Purpose: First to look at the expectations of pharmacy staff relating to the structural reorganisation needed as a result of the implementation of a TQMS, and second to gather suggestions for quality improvements in their everyday work. Materials and Methods: Data collection was achieved using a non-disguised questionnaire consisting of 8 questions. Two open-ended questions (unstructured, key ideas), five closed-ended dichotomous questions (followed by contingency questions) and one question using a rating scale from one to ten were asked. All staff members of the pharmacy were asked to fill out the survey. For data evaluation a Grounded Theory-based coding system was used. Results: Establishing a TQMS was deemed to be important by 90.5% of the respondents. A total of 21 usable responses were received, for a response rate of 72.4%. The areas in which a TQMS was deemed to be important were: improvements of work processes (∼30%), quality control (∼20%), communication (∼15%) and training (∼10%). Further we found that the respondents wanted to improve quality in work processes, through implementation of regular training (∼20%), better communication (∼15%) and better working conditions (∼15%). Conclusions: From this project we can state clearly that pharmacy staff welcomes the introduction of a TQMS to their workplace. TQMS was expected to be most important for improving work processes. The frequency of importance of communication and training being highlighted by the respondents was of interest and should be borne in mind during the implementation process. No conflict of interest.